Improved plant resistance to drought is promoted by the root‐associated microbiome as a water stress‐dependent trait. (25th March 2014) - Rolli, Eleonora; Marasco, Ramona; Vigani, Gianpiero; Ettoumi, Besma; Mapelli, Francesca; Deangelis, Maria Laura; Gandolfi, Claudio; Casati, Enrico; Previtali, Franco; Gerbino, Roberto; Pierotti Cei, Fabio; Borin, Sara; et al.
Summary Although drought is an increasing problem in agriculture, the contribution of the root‐associated bacterial microbiome to plant adaptation to water stress is poorly studied. We investigated if the culturable bacterial microbiome associated with five grapevine rootstocks and the grapevine cultivar Barbera may enhance plant growth under drought stress. Eight isolates, over 510 strains, were tested in vivo for their capacity to support grapevine growth under water stress. The selected strains exhibited a vast array of plant growth promoting (PGP) traits, and confocal microscopy observation of gfp‐labelled Acinetobacter and Pseudomonas isolates showed their ability to adhere and colonize both the Arabidopsis and grapevine rhizoplane. Tests on pepper plants fertilized with the selected strains, under both optimal irrigation and drought conditions, showed that PGP activity was a stress‐dependent and not a per se feature of the strains. The isolates were capable of increasing shoot and leaf biomass, shoot length, and photosynthetic activity of drought‐challenged grapevines, with an enhanced effect in drought‐sensitive rootstock. Three isolates were further assayed for PGP capacity under outdoor conditions, exhibiting the ability to increase grapevine root biomass. Overall, the results indicate that PGP bacteria contribute to improve plant adaptation to drought through a water stress‐induced promotion ability.